Muscle respiratory training in neurocritical patient with prolonged mechanical ventilation - Garcìa, Adriana Monsalve (2019)
Mechanical ventilation is frequently established in patients admitted to intensive care units. Although its use in most cases is transient, from 32% to 41% of neurocritical patients require it for prolonged periods due to various conditions that make it difficult to wean. In circumstances in which the cause of its prolongation is muscle weakness, inspiratory muscle training is important, which can contribute to the increase of muscularstrength and facilitate weaning. The objective of this report is to describe the case of a 65-year-old patient with Fisher III subarachnoid hemorrhage, prolonged mechanical ventilation and difficulty in weaning in whom a respiratory muscle training strategy was implemented.